DAGUSIBU Drug Management Counseling (Get, Use, Save, Dispose) in Banjar Kodok Darsana, Karangasem Regency - Dira, Made Asmarani; Puspitasari, Lia (Jurnal Abdimas ITEKES, 2021)
Dagusibu is one of the efforts to improve health for the community which is carried out through health service activities by pharmaceutical personnel. Health services that can be provided by pharmacists to the community include, among others, providing information on the use and storage of pharmaceutical preparations and medical devices. People need to know the importance of managing drugs from getting prescriptions to throwing them away if they are not needed. Thus, the impact of community abuse errors can be prevented. Lack of public curiosity about this is very dangerous. They should not underestimate the procedures for drug management. Starting from the beginning they get a prescription from a doctor, to how to dispose of it if it can no longer be used. In fact, if we mismanage the drug a little, it will be very fatal for the consumer of the drug. The results of counseling on Dagusibu Drug Management (Get, Use, Save, Dispose) in Banjar Kodok Darsana, Karangasem Regency can provide insight and education on drug management from getting prescriptions to throwing them away if not needed. Thus, the impact of community abuse errors can be prevented. Participants can apply the knowledge that has been obtained in the family and community environment.